Psychological factors contributing towards financial problem among civil service sector employees - Abdul Rahim @ Abdul Wahab, Husniyah; Magli, Amirah Shazana; Sabri, Mohamad Fazli; Othman, Mohd Amim; Mohd Rasdi, Roziah (Malaysian Consumer and Family Economics, 2020)
Financial problems faced by employees can affect their performance and life satisfaction, as well as impact people surrounding them. This study aimed at identifying the potential contributors to financial problems among employees, whereby multi-stage random sampling was used to sample employees working in the civil service sector of Peninsular Malaysia. The results obtained from 470 employees in this cross-sectional study revealed that psychological factors such as self-worth, future orientation, locus of control, and materialism were more prevalent in contributing to their financial problems. In particular, self-worth and future orientation negatively contributed to financial problems, whereas locus of control and materialism were contrastingly revealed as posing positive influences on the aspect. Meanwhile, financial behaviours such as savings and investment were not contributing directly to financial problem in consideration of psychological factors, wherein these employees’ perception of financial adequacy could be attributed instead. Hence, an intervention programme for employees focusing on these psychological factors can be developed by vigilant employers in enhancing their performance. Here, successfully overcoming employee’s financial problems may further benefit both parties, thereby leading to explosive economic growth.